Olgularla Nörolojik Yoğun Bakım - Çubuk, Can; Demir, Turgay; Aydın, Kaniye; İnal, Seza; Kibar, Filiz; C. İnal, Tamer; Kaya, Ömer; Dik, Berkay; Akgül, Erol; Aslan Kara, Kezban; Elçin Ateş, Başak; Bilen Onan, Hasan; et al. (2024)
-